Research on Market Competition and Firm Performance: A Systematic Literature Review (2020–2024) - Khairil Anwar; Tussi Sulistyowati; Pardomuan Pardosi; Agtovia Frimayasa; Novy Fitria (Indonesia Journal of Engineering and Education Technology (IJEET), 2025)
This paper employs a systematic literature review (SLR) rooted in the PRISMA methodology to investigate the interaction between market competition and firm performance based on 2020-2024 peer-reviewed articles published on the Web of Science database. Out of the original 105 articles, 24 empirical studies were selected based on strict filtering criteria and then analyzed according to methodology, region, theory, and main findings. Evidence shows that market competition has a tendency to enhance firm performance but with different impacts depending on internal factors of the firm, including capital structure, managerial quality, governance, and leadership, as well as external factors like institution quality and industry circumstances. These include agency theory, resource-based perspective, dynamic capabilities, contingency theory, and upper echelons theory. Implications highlight the need for leadership and governance convergence with the demands of the market and investments in dynamic capabilities to be competitive, especially in innovation-driven and scarcity environments. Future research will have to examine longitudinal effects across business cycles, the potential of digitalization, and use mixed methods or meta-analyses to enhance insight by industry and region.